Estudo da viabilidade econômica da implantação de coberturas termoacústicas com painéis fotovoltáicos em edificações: estudo de caso em uma instituição de ensino superior - BRAZ, Sérgio Cabeça (Universidade Federal do Pará, 2018)
With the evolution of humanity and the appearance of new technologies in civil construction combined with the need for environmental comfort, reduction of environmental impacts and consumption of electricity, it becomes indispensable to use new materials and sources of renewable energy in buildings for reduction costs and environmental impacts. In this scenario, the coverage of the buildings of a higher education institution in the state of Pará was studied aiming at the environmental comfort and reduction of costs in the consumption of electric energy. Exploratory research was carried out, considering the area of the building, type of coverage, the consumption of electric energy and calculations through the projected cash flow with a time horizon of 25 years compatible with the useful life of the system. We thus obtained discounted cash flow, payback and net present value. The results showed that the use of the thermoacoustic tile in the roofs with the implantation of the photovoltaic solar energy system as an alternative for cost reduction is feasible for the studied buildings with a saving of around 13%, time of return 12/13 years (50% of the system's useful life) and NPV of, on average, 44% of the initial investment. For the covered walkways of the Institution that in its totality is approximately 5km, the implantation of the photovoltaic system was not viable.